SAXSMoW 3.0: New advances in the determination of the molecular weight of proteins in dilute solutions from SAXS intensity data on a relative scale - de Oliveira Neto, Mario [UNESP]; de Freitas Fernandes, Adriano; Piiadov, Vassili; Craievich, Aldo Felix; de Araújo, Evandro Ares; Polikarpov, Igor (Wiley, 2022)
SAXSMoW (SAXS Molecular Weight) is an online platform widely used over the past few years for determination of molecular weights of proteins in dilute solutions. The scattering intensity retrieved from small-angle X-ray scattering (SAXS) raw data is the sole input to SAXSMoW for determination of molecular weights of proteins in liquid. The current updated SAXSMoW version 3.0 determines the linear dependence of the true protein volume on their apparent protein volume, based on SAXS curves calculated for 67,000 protein structures selected from the Protein Data Bank. SAXSMoW 3.0 was tested against 43 experimental SAXS scattering curves from proteins with known molecular weights. Our results demonstrate that most of the molecular weights determined for the nonglycosylated and also for the glycosylated proteins are in good agreement with their expected molecular weights. Additionally, the average discrepancies between the calculated molecular weights and their nominal values for glycosylated proteins are similar to those for nonglycosylated ones.